The Adoption of Internet of Things in Urban Farming. - Salim, Siti Aisyah; Sa’don, Nurul Shafinaz (Research in Management of Technology and Business, 2021)
Urban farming is one of the initiatives to supply urban residents with fresh vegetables and animal products. Further, with the right usage of technologies such internet of things (IoT) for urban activities could enhance the quality crops, reduced expenses and monitor plants and crops in real time. Limited of space is one major concern that widely discussed in past studies in relation to urban farming activities. However, discussion on the practicality and the usage of technologies in relation to urban farming activities still very lack in the context of Malaysia. Thus, the aim of this study is to identify the most dominant factor that influence IoT adoption in urban farming. Technology Acceptance (TAM) and Theory of Planned Behavior (TPB) have been adopted as theoretical foundation in this research. This study has collected 110 respondents among city residents in Johor Bahru. The sample was collected based on quantitative research method where self-administrated questionnaire has been applied. From the analysis, it shows that subjective norms factor has the most dominant influence towards IoT adoption in urban farming with average mean value 4.37. This study gives significant impact to several parties including (i) policy maker in order to promote and support urban farming in Malaysia; (ii) to farmers especially for giving the understanding on factors that could influence the adoption of IoT; (iii) to future researchers to study further about current technology and the importance of cultivation and also can be practice in future.